The Contribution of Body Measurements to the Skill Performance of Female Students in Basketball at the College of Physical Education and Sports Sciences, University of Hamdaniya - Shihab Al-Dhaher; Diaa Ibrahim (Universitas Negeri Jakarta, 2025)
ABSTRACT The aim of the research was to identify the relationship between body measurements and skill performance in basketball and to identify the contribution of body measurements to skill performance in basketball among female students in the College of Physical Education and Sports Sciences, University of Hamdaniya. A descriptive approach was used with a correlational approach due to its suitability to the nature of the research. The research community was defined as the students of the College of Physical Education and Sports Sciences, University of Hamdaniya (2024-2025), numbering (197) male and female students. The research sample was selected using a stratified approach from the first, second, third, and fourth stages, totaling (52) female students. To achieve the research objectives, the following measurements were used (standing height, leg length, arm length, palm length, abdominal circumference, hip circumference, upper arm circumference, chest circumference, thigh circumference, and leg circumference). To arrive at the results, statistical methods were used (arithmetic mean, standard deviation, simple correlation coefficient (Pearson), multiple correlation coefficient, and percentage). The research reached the following conclusions: Generally, body measurements contributed insignificantly to the skill performance of female students in the Department of Physical Education and Sports Sciences at the College of Education for Pure Sciences, Al-Hamdaniya University. Body weight represented an influential contributor to the skill performance of female students in the Department of Physical Education and Sports Sciences at the College of Education for Pure Sciences, Al-Hamdaniya University. A prediction equation for body weight of (9%) was obtained. In light of this, the researchers made a number of recommendations. Keyword: Body Measurements, Skill Performance, Basketball ABSTRAK Tujuan penelitian adalah untuk mengidentifikasi hubungan antara ukuran tubuh dengan performa keterampilan dalam bola basket dan untuk mengetahui kontribusi pengukuran tubuh terhadap performa keterampilan dalam bola basket pada mahasiswi di Sekolah Tinggi Pendidikan Jasmani dan Ilmu Olah Raga Universitas Hamdaniya. Pendekatan yang digunakan adalah pendekatan deskriptif dengan pendekatan korelasional karena kesesuaiannya dengan sifat penelitian. Komunitas penelitian ditetapkan sebagai mahasiswa Sekolah Tinggi Pendidikan Jasmani dan Ilmu Olah Raga Universitas Hamdaniya (2024-2025) yang berjumlah (197) mahasiswa laki-laki dan perempuan. Sampel penelitian dipilih dengan pendekatan stratified dari tahap pertama, kedua, ketiga, dan keempat yang berjumlah (52) siswi. Untuk mencapai tujuan penelitian maka digunakan pengukuran sebagai berikut (tinggi berdiri, panjang tungkai, panjang lengan, panjang telapak tangan, lingkar perut, lingkar pinggul, lingkar lengan atas, lingkar dada, lingkar paha, dan lingkar tungkai). Untuk mencapai hasil tersebut digunakan metode statistik (rata-rata aritmatika, simpangan baku, koefisien korelasi sederhana (Pearson), koefisien korelasi berganda, dan persentase). Penelitian ini mencapai kesimpulan sebagai berikut: Secara umum, pengukuran tubuh memberikan kontribusi yang tidak signifikan terhadap kinerja keterampilan mahasiswi di Jurusan Pendidikan Jasmani dan Ilmu Olah Raga di Sekolah Tinggi Pendidikan Ilmu Pengetahuan Murni, Universitas Al-Hamdaniya. Berat badan merupakan kontributor yang berpengaruh terhadap kinerja keterampilan mahasiswi di Departemen Pendidikan Jasmani dan Ilmu Olah Raga di Sekolah Tinggi Pendidikan Ilmu Pengetahuan Murni, Universitas Al-Hamdaniya. Persamaan prediksi berat badan (9%) diperoleh. Sehubungan dengan hal tersebut, para peneliti memberikan beberapa rekomendasi. Kata Kunci: Pengukuran Tubuh, Skill Performance, Bola Basket